1997
DOI: 10.1080/00087114.1997.10797383
|View full text |Cite
|
Sign up to set email alerts
|

Morphological aspects of early host-parasite interactions in infections ofMelampsora pinitorquaandMelampsora larici-tremulaeonPinus sylvestris.Implications in the taxonomical relationship of the two rust fungi

Abstract: A cyto-histological study was carried out on Pinus sylvestris seedlings artificially infected with basidiospores of Melampsora pinitorqua and Melampsora laricitremulae, in order to differentiate between the two rust fungi and delineate their taxonomical relationships. The general morphology of the early phases of the majority of infections of Melampsora larici-tremulae on P. sylvestris show similar characteristics to those of M. pinitorqua. Moreover, in M. larici-tremulae / P. sylvestris interactions, the foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 47 publications
0
6
0
1
Order By: Relevance
“…Indeed, owing to the partial overlapping of the host range of M. pinitorqua and M. larici-tremulae described in previous works by Longo et al (1970;1975), a basidiospore-derived direct penetration was shown also in the following cases of inoculations: 1) M. larici-tremulae on growing shoots of P. sylvestris (Longo et al 1997); 2) M. pinitorqua on growing needles from brachiblasts of Larix decidua (Moricca et al 2003); 3) M. larici-tremulae on cotyledons and primary needles of P. pinea (Moricca et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, owing to the partial overlapping of the host range of M. pinitorqua and M. larici-tremulae described in previous works by Longo et al (1970;1975), a basidiospore-derived direct penetration was shown also in the following cases of inoculations: 1) M. larici-tremulae on growing shoots of P. sylvestris (Longo et al 1997); 2) M. pinitorqua on growing needles from brachiblasts of Larix decidua (Moricca et al 2003); 3) M. larici-tremulae on cotyledons and primary needles of P. pinea (Moricca et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…However, subsequent studies on the penetration of the basidiospore germ tubes of sev eral rust fungi on their hosts (MILLER et al 1980;GRAY et al 1983;GOLD andMENDGEN 1984, 1991;HOPKIN et al 1988; LONGO et al 1988LONGO et al , 1991LONGO et al , 1994LONGO et al , 1997MORIN et al 1992) confirmed direct penetration for these spores and consid ered the indirect penetration of (i) C.ribicola on P.strobus (PATTON and JOHNSON 1970) and (ii) Cronartium comandrae Pk. on Pinus banksiana Lamb.…”
Section: Introductionmentioning
confidence: 99%
“…appendiculatus by GOLD and MENDGEN (1984), for Puccinia xanthii Schw. by MORIN et al (1992), for Melampsora pulcherrima (Bub) Maire by LONGO et al (1994), for M. pimtorqua and M. larici tremulae by LONGO et al (1997), is made up of a thin neck which de rives from the penetration peg and of a widened portion with a large central vacuole. In accord ance with what has been observed in the substomatal vesicle of C. flaccidum, also in the intraepidermal one there is no septum to separate the infection peg from the vesicle; only in C. quercuum f. sp.…”
Section: Colonization During Early Symptoms On the Needlesmentioning
confidence: 99%
See 2 more Smart Citations